Impact of acclimatization system on zootechnical performance and thermal comfort in young broiler chickens (Research, Society and Development, 2020)
Regulating room temperature of poultry houses is frequently difficult for breeders; nevertheless, it is very important that housing provides a comfortable thermal environment for chicks. Therefore, the objective of this work was to compare environmental aspects of two rearing systems in broiler chicks aged 1 to 21 days, as well as batch productivity throughout the production cycle (1-42 days). The experimental design was randomized blocks, with two types of shed: one with a positive pressure system and one with negative pressure system. The average weights at 7, 14, and 21 days were measured, as was final slaughter weight and feed conversion. We found a higher internal temperature in the negative pressure system at 7, 14, and 21 days, and maintaining the birds within the temperature considered ideal for thermal comfort at their ages. Regarding relative humidity, only at 14 days was there a difference between the systems, in which the negative pressure system maintained better humidity than did the positive pressure system. Both systems maintained litter temperature within the recommended range for the chicks’ ages; however, there were differences between the systems on days 7 and 21. Litter moisture showed a difference only at 14 days of age; however, both systems were within the optimal range. Ammonia concentrations in the poultry houses showed no differences between the two types of treatment. There was also no significant difference between the acclimatization systems for drinking water temperature and water consumption. The average weight of the 7-day-old chicks differed between the acclimatization systems, with higher weights in the negative pressure system than in the positive pressure system. We measured higher average slaughter weight and lower feed conversion in broiler chicks raised in the negative pressure system. We conclude that the negative pressure system enhanced the productive performance of chickens and improved thermal comfort.